2004
DOI: 10.1016/j.biopha.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of carotenoids in the prevention of human pathologies

Abstract: Reactive oxygen species (ROS) and oxidative damage to biomolecules have been postulated to be involved in the causation and progression of several chronic diseases, including cancer and cardiovascular diseases, the two major causes of morbidity and mortality in Western world. Consequently dietary antioxidants, which inactivate ROS and provide protection from oxidative damage are being considered as important preventive strategic molecules. Carotenoids have been implicated as important dietary nutrients having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
332
0
22

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(356 citation statements)
references
References 141 publications
2
332
0
22
Order By: Relevance
“…The cancer-preventive capacities of carotenoids are attributed to their anti-oxidant capacities and their effect on gap junctional communication which play a role in the regulation of cell growth, differentiation and apoptosis [67]. It has been demonstrated that carotenoids influence the proliferative capacity and differentiation of mammary epithelial cells [68].…”
Section: Biological Mechanismmentioning
confidence: 99%
“…The cancer-preventive capacities of carotenoids are attributed to their anti-oxidant capacities and their effect on gap junctional communication which play a role in the regulation of cell growth, differentiation and apoptosis [67]. It has been demonstrated that carotenoids influence the proliferative capacity and differentiation of mammary epithelial cells [68].…”
Section: Biological Mechanismmentioning
confidence: 99%
“…It has many biochemical functions as a highly efficient antioxidant and free radical scavenging agent and inhibitor of proinflamatory and pro-thrombotic factors (Cohen, 2002;Tapiero et al, 2004;Velmurugan et al, 2004;Mordente et al, 2011). It is twice as effective as β-carotene and 10-fold more activethan α-tocopherol as an antioxidant (Di Mascio, 1989) provides protectionagainst cellular damage caused by reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are frequently consumed fresh, over 80% of tomatoes are consumed as processed products such as tomato juice, paste, pure, ketchup and sauce (Gould 1992). Recent studies have indicated the potential health benefits of a diet rich in tomatoes and tomato products (Tapiero et al 2004). Tomato and tomato products are the major sources of lycopene and are considered to be important contributors of carotenoids in human diet (Tapiero et al 2004;Goula and Adamopoulos 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated the potential health benefits of a diet rich in tomatoes and tomato products (Tapiero et al 2004). Tomato and tomato products are the major sources of lycopene and are considered to be important contributors of carotenoids in human diet (Tapiero et al 2004;Goula and Adamopoulos 2005). They are rich in lycopene and other carotenoids such as β-carotene, phytoene, phytofluene and lutein (Choski and Joshi 2007;Kavanaugh et al 2007).…”
Section: Introductionmentioning
confidence: 99%